STATUS DAN KENEKARAGAMAN FUNGI MIKORIZA ARBUSKULA (FMA) PADA TANAH BEKAS KEBAKARAN HUTAN DI KABUPATEN SAMOSIR - Lusi Astri Simamora; Deni Elfiati; Delvian Delvian (Peronema Forestry Science Journal, 2015)
Arbuscular Mycorrhizal Fungi (AMF) are cosmopolitan is almost found in a variety of ecosystems. Forest fires influence the biological properties of the soil, especially AMF. This research aims to study the status and diversity of AMF in the former soil of forest fires. Samples of soil and roots of plants was taken from the location of the fire in separate incidents during the 5 period and location unburn. Parameters observed that the degree of root infection, spores density and identification of the type of spores. Identification of mycorrhizae conducted at the Laboratory of Soil Biology, Faculty of Agriculture, University of North Sumatra, begin in May until September 2014. Morphology characteristics used to identify the type of AMF is a form of cell wall thickness, presence or absence of substanding hyphae, surface smoothness and spores  reaction to melzers. The results show that an increase in the average density of spores from the field and the results of trapping, for the average percentage of AMF colonization in the roots of plants at 50,65% include grade 3 and 4 or high categories. Found 2 genus, namely Genus Acaulospora and Genus Glomus. Of the field found as many as 35types of spores and trapping results are found as many as 40 types of spores. Key words: Arbuscular Mycorrhizal Fungi (AMF), Forest fire